The economics of soil conservation in development countries: The case of crop residue mulching. - Erenstein, Olaf (Wageningen University & Research, 1999)
The study contributes to the search for a methodology to assess soil conservation, particularly in developing countries. The study first assesses the economics of soil conservation in general - with special emphasis on the relationships between technology, economic analysis and policy implications. The quantification and valuation of soil erosion and soil conservation are highly controversial and present considerable analytical challenges that have been tackled in varying ways. By implication, government intervention is controversial too - and has typically been unsuccessful. This has direct implications for both the development of conservation technology and the implementation of conservation interventions.The study subsequently assesses the economics of one particular technological conservation option: crop residue mulching (also known as conservation tillage). An analytical framework is developed to assess the socio-economics of the technology in developing countries. The technology assessment framework follows a stepwise expanding analysis along a three-tier hierarchy: crop production, the farm household and the institutional setting. This results in a private and a social assessment of the technology, and the formulation of corresponding policy implications. The framework is applied in ex ante , ex post and partial analyses of crop residue mulching in different settings in Mexico and Central America. Conclusions are drawn regarding the technology assessment framework and crop residue mulching.The author can be contacted at: olaf_erenstein@usa.net The study is also published in the Mansholt Studies, Wageningen University and can be ordered from Backhuys Publishers, Leiden, the Netherlands (http://www.backhuys.com , or info@backhuys.com).